Service Quality, Price, and Brand Image Influencing Consumer Purchase Intention - I Gusti Bagus Agastya Putra; Made Setini; Bayu Pasupati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
This study examines the influence of service quality, price, and brand image on consumer purchase intention at M. Aboe Talib Coffee Shop in East Denpasar. The research is motivated by inconsistencies in previous findings and a decline in visitor numbers, indicating the need to better understand factors affecting consumer interest. A quantitative approach was employed using a survey method. Data were collected through questionnaires distributed to 100 respondents, selected using the Slovin formula and purposive sampling technique. The collected data were analyzed using multiple linear regression, supported by t-tests and F-tests to examine partial and simultaneous effects among variables. The results show that service quality, price, and brand image simultaneously have a positive and significant effect on consumer purchase intention. Partially, each variable also demonstrates a positive and significant influence on purchase intention. These findings indicate that improving service performance, offering competitive and value-based pricing, and strengthening brand image are essential strategies for increasing consumer interest in the coffee shop industry. This study contributes empirically by highlighting the importance of integrating service quality, price perception, and brand image to enhance consumer purchase intention, particularly for traditional coffee shops facing intense competition from modern coffee shop trends. The results provide practical implications for business owners in developing effective marketing strategies to attract and retain customers.